Decay of the vortex tangle at zero temperature and quasiclassical turbulence: Квантованные вихри и турбулентность - Nemirovskii, Sergey K. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
We review and analyze a series of works, both experimental and numerical and theoretical, dealing with the decay of quantum turbulence at zero temperature. Free decay of the vortex tangle is a key argument in favor of the idea that a chaotic set of quantum vortices can mimic classical turbulence, or at least reproduce many of the basic features. The corresponding topic is referred as the quasiclassical turbulence. Appreciating significance of the challenging problem of classical turbulence it can be expressed that the idea to study it in terms of quantized line is indeed very important and may be regarded as a breakthrough. For this reason, the whole theory, together with the supporting experimental results and numerical simulations should be carefully scrutinized. One of the main arguments, supporting the idea of quasiclassical turbulence is the fact that vortex tangle decays at zero temperature, when the mutual friction is absent. Since all other possible mechanisms of dissipation of the vortex energy, discussed in literature, are related to the small scales, it is natural to suggest that the Kolmogorov cascade takes place with the flow of the energy in space of scales, just like as in the classical turbulence. In the present work we discuss an alternative mechanism of decay of the vortex tangle, which is not associated with dissipation at small scales. This mechanism is a diffusive-like spreading of the vortex tangle due to evaporation of small vortex loops. We discuss a number of experiments and numerical simulations, considering them from the point of view of alternative mechanism.